Research on the planting status and development of herbal medicine industry in Lantian County under the background of modern technology development - Yang, Yuxin (International Journal of Global Economics and Management, 2024)
Lantian County in Shaanxi Province has abundant natural herbal resources, and the development of the herbal planting industry is closely related to the people’s livelihood in the planting areas of Lantian County, which is crucial for the implementation of the rural revitalization strategy. With the popularization of Internet technology and the development of digital infrastructure, modern technology has become a powerful guarantee for the prosperity of rural industries, the modernization of agriculture and rural areas, and poverty alleviation. It is also an effective power to promote the planting and development of herbal medicine industry in Lantian County. In order to further accelerate the pace of modern technology enabling herbal medicine planting, this paper analyzes the problems existing in the development of the herbal medicine planting industry in Lantian County based on the current situation of the development of the herbal medicine planting industry in Lantian County, makes in-depth analysis from three aspects of planting mode, sales channels and industrial influence, and explores the path to the prosperity of the herbal medicine planting industry in Lantian County under the background of modern technology development, providing theoretical reference for the poverty alleviation of Lantian County, It also provides ideas and references for the development of herbal planting industries in other regions of China.